2020
DOI: 10.3329/sja.v17i2.45305
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Divergence In Tomato Germplasm

Abstract: Phenotypic divergence was quantified by multivariate analysis among the 70 genotypes collected from different agro-climatic regions and was available in the gene bank of Energypac Agro Ltd., Gazipur, Bangladesh. Based on the phenotypic value of 11 characters, 70 genotypes were grouped into five clusters. The genotypes of tomato were distributed in different clusters suggesting that no association was found between geographical and phenotypic diversity. Cluster II consisted of maximum twenty three genotypes (32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Some researchers found similar cluster pattern with 40 segregating hybrids of tomato (Ghosh et al, 2009). In a study with seventy genotypes, similar clustering was reported (Ullah et al, 2019). In a previous study, 23 tomato genotypes were grouped into five distinct clusters considering fourteen yield and yield related traits (Alam et al, 2020).…”
Section: Principal Component Analysissupporting
confidence: 59%
“…Some researchers found similar cluster pattern with 40 segregating hybrids of tomato (Ghosh et al, 2009). In a study with seventy genotypes, similar clustering was reported (Ullah et al, 2019). In a previous study, 23 tomato genotypes were grouped into five distinct clusters considering fourteen yield and yield related traits (Alam et al, 2020).…”
Section: Principal Component Analysissupporting
confidence: 59%